Isolation of antifungal bacteria from compost and environmental samples - Sim, Jolene Xin Ying (Nanyang Technological University, 2020)
Basal stem rot (BSR) disease caused by Ganoderma boninense infects oil palms and is spreading rapidly in oil palm plantations. This has caused resources to be wasted and resulting economic losses. Much effort has been put into finding a cure for the disease, but no effective method has been reported yet - with many only being able to slow the death of infected oil palms. In recent years, the use of biocontrol agents has been explored, prompting more extensive research to be done. In this project, bacterial strains from environmental and compost samples that inhibited the growth of G. boninense were isolated and examined. They were used to construct a phylogenetic tree based on their 16s rRNA gene distance. Metabolites responsible for the inhibition derived from each of the isolated bacterial strains were studied as well.